The Causes of Long Waiting Times for Outpatient Pharmaceutical Prescription Services at Hospital “X” in Padang - Adila Kasni Astiena; Mutia Khairunnisa; Kamal Kasra; Fadilla Azmi (Fakultas Farmasi Universitas Andalas, 2022)
Outpatient pharmacy services in a hospital shows the quality of health service to the community. Data from the internal quality assurance report of Hospital ”X” in Padang showed that only 93.76% of non-compounded medication and 94.6% of compounded medication recipes met the waiting time standard. This study aimed to analyze the causes of the long waiting time for outpatient pharmacy services at Hospital “X”. The type of this research was a mix-method sequential type explanatory, conducted from February until May 2022. The quantitative design was a cross-sectional study of 141 for non-concoction and 35 for compounded medication recipes determined by quota sampling. Qualitative research was conducted on seven informants by purposive sampling. Observation, in-depth interviews, and document review collected data. Results showed that the average waiting time was 84.19 (standard ≤30) minutes for non-concoction and 164.58 (standard ≤60) minutes for compounded medication recipes. The causes of the long waiting time were a need for more staff, prescriptions outside the hospital formulary, equipment errors, and medicines delivery delays. There should be a job redesign by rearranging the shift picket for pharmacy staff, regular equipment maintenance, and updating standard operating procedures related to medicines delivery to the patients.